Differentiation and integration: students' mistake and the correction / Maisurah Shamsuddin - Shamsuddin, Maisurah (Unit Penerbitan JSKM, 2020)
Calculus 1 and Calculus 2 are compulsory subjects for Engineering students in UiTM Penang. The mathematics course codes involving these two topics are MAT183 for semesters 1 or 2 and MAT235 for semesters 2 or 3. Each semester the student's weaknesses can be identified based on the topic differentiation which is learned in the subject of calculus 1 or MAT183. In this chapter, I will share a little bit of knowledge to correct what is wrong with examples of student error in the step of calculation for differentiation and integration.